Evaluation and treatment of pulsatile tinnitus associated with sigmoid sinus wall anomalies. (14th May 2018) - Eisenman, David J.; Raghavan, Prashant; Hertzano, Ronna; Morales, Robert
Abstract : Objective: Describe clinical and radiographic features of sigmoid sinus wall anomalies (SSWA) associated with pulsatile tinnitus (PT) and determine factors predictive of response to surgery. Methods: Preoperative diagnostic imaging and treatment response were reviewed after surgical repair of 40 ears among 38 consecutive patients presenting with PT associated with SSWA who underwent transtemporal sinus wall reconstruction. Results: Twenty‐three ears had isolated sigmoid sinus dehiscence, and 17 had diverticulum. The rates of transverse sinus stenosis (TSS) and empty sella, 66% and 32% respectively, were significantly higher than in historical controls ( P = 0.02 and 0.001). Thirty‐six out of 40 subjects (90%) had complete resolution of their PT following surgery, including all those with a diverticulum. For subjects with dehiscence alone without diverticulum, a favorable response to surgery was strongly associated with the presence of TSS ( P = 0.01) and empty sella ( P = 0.02). Conclusion: Sigmoid sinus diverticulum and dehiscence are a clinically important cause of PT. Women of childbearing age with an elevated body mass index (BMI) are commonly affected, and there is a high rate of associated TSS and empty sella. Transtemporal sinus wall reconstruction has a high rate of success in appropriately selected patients. Patients with isolated sinus wall dehiscence without diverticulum, TSS, or empty sella are less likely to respond to transtemporal sinus wall reconstruction. These data imply a multifactorial cause of PT in at least some patients with SSWA. Level of Evidence: 4 Laryngoscope, 128:S1–S13, 2018